Utilization of Chicken Eggshells as Catalyst in Biodiesel Synthesis from Waste Cooking Oil: Chicken Eggshells as Catalyst in Biodiesel Synthesis from Waste Cooking Oil - Mawarani, Lizda Johar; Sihombing, Thomas Andherson; Risanti, Doty Dewi; Massadeh, Muhannad Illayan; Prananto, Dwi (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Solid oxides are the most used catalyst for the synthesis of biodiesel, one of which is calcium oxide (CaO). This research reports the synthesis of CaO catalysts sourced from chicken eggshells through the calcination process. Chicken eggshells were cleaned and dried for 24 h at 120 oC. The eggshells were then calcined at temperatures varying from 600 oC to 900 oC for 6 h and the resulted sample were characterized by FTIR and XRD. The biodiesel synthesis was conducted at 65 ºC with a reaction time of 2 h and the concentration of catalyst was varied at 3 wt%, 6 wt%, and 9 wt%. The optimal biodiesel synthesis was obtained at a concentration of CaO catalyst formed at a calcination temperature of 900 ºC at 9 wt%. The yield of biodiesel conversion was obtained at 81.43 % and glycerol was produced as a by-product.